Processing poly(ether etherketone) an a 3D printer for thermoplastic modelling - Valentan, Bogdan (Materiali in tehnologije, 2013)
PEEK, poly(ether etherketone), is one of the high-quality industrial polymers. It is widely used in extremely demanding areas like automotive, aircraft and space industries. Because of the fact that it is bio-compatible, PEEK is also used for medical implants that are usually made by milling a block of the material. The article presents the results of an investigation of processing PEEK on a 3D printer for thermoplastic modelling. The used procedure is one of the additive manufacturing procedures and, as such, it builds a product by adding material layer by layer to get the finished product. Commercially available machines are unable to achieve the required melting and environment temperatures, so a new machine was developed. The machine was designed and built at the company Ortotip d.o.o. and it is able to produce the parts of up to 130 mm Ž 130 mm Ž 150 mm. After the initial testing, test specimens, according to standards EN ISO 527-2: 2012 and EN ISO 178: 2011, were produced and tested at the facilities of the PEEK manufacturer Invibio (from the UK). The article presents the steps taken when developing the PEEK modelling machine, the test methods to verify the mechanical properties of manufactured products and the results of the material testing. The machine was developed to produce medical implants (specific maxillofacial prosthesis), but with additional testing (that will help to improve the mechanical properties of produced parts) practically all bone-replacement implants can be made.
Keywords: polimeri; 3D-tiskanje; vsadki; termoplasti; biokompatibilnost; dodajalne tehnologije